Reporte de caso con 14 meses de seguimiento - Estacio Gallegos, Adriam Ivan (2024)
Objective: Describe the tri-antibiotic performance by clinic and radiographic evaluation in a conventional pulpectomy during a 14-month period. Case Report: A 5-year and 10-month-old female patient attended Universidad Cientifica del Sur’s (Lima, Perú) Dental Clinic accompanied by her mother who requested a general evaluation. Clinical examination revealed multiple carious lesions and irreversible pulpitis in dental piece 75 was diagnosed. Treatment plan included a pulpectomy in two appointments (mainly driven by patient’s negative behavior). However, in the last appointment a conventional pulpectomy treatment was decided placing tri-antibiotic paste only at the entrance of the canals and floor of the pulp chamber of tooth 75, since it had already been partially instrumented. Subsequently, patient had periodic check-ups and after a 14-month follow-up, tooth 75 clinically did not present symptoms and radiographically the preservation of the root tissues was observed. Conclusion: The use of tri-antibiotic paste applied only to the entrance of the canals and floor of the pulp chamber in conventional pulpectomy treatment demonstrated good clinical and radiographic performance at 14 months of follow-up.